RESULTS OF THE MINIMAX PRINCIPLE FOR SELF-ADJOINT OPERATORS IN THE FRIEDRICHS MODEL - Davron Kulturayev Jurayevich; Bakhriddin Oltiyev Jurayevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The discrete spectrum of self-adjoint operators in the Friedrichs model is studied. A sufficient condition for the existence of an infinite number of eigenvalues ​​of the Friedrichs model is given. It is proved that the negative eigenvalues ​​of the discrete Schrödinger operator are infinite.